Methodology for using electronic resources to develop grammatical competence in primary school students - Turakulova Lola Xamidjanovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: The rapid integration of digital technologies into primary education has opened new opportunities for enhancing grammatical competence among young learners. This thesis explores a systematic methodology for utilizing electronic resources—such as interactive apps, online platforms, multimedia tools, and educational software—to develop grammatical skills in primary school students (ages 6–10). The approach emphasizes interactive, game-based, and personalized learning to make grammar acquisition engaging and effective. Empirical evidence from recent studies indicates that digital tools improve motivation, provide immediate feedback, and support differentiated instruction, leading to better grammatical accuracy and usage in both oral and written forms. The methodology combines traditional grammar presentation with active practice through digital means, addressing challenges like short attention spans and varying proficiency levels in young children.